Tumours and tumour-like lesions of the spinal canal and spine. A review of 185 consecutive cases with more detailed close-up on some chosen pathologies - Kwinta, Borys; Adamek, Dariusz; Moskała, Marek; Stachura, Krzysztof (Polish Journal of Pathology, 2011)
Objectives : Spinal canal tumours constitute a minor part of CNS invading neoplasm. However, due to their damaging influence on the spinal cord and the spinal roots, they cause serious clinical problems and can lead to severe disability. The aim of this study is to review material collected on tumours of the spine and the spinal canal at the Department of Neuropathology over the past ten years. Material and methods : One hundred and eighty five histopathological examinations of spinal tumours were evaluated between August 1997 and August 2007. The group of patients included 94 females and 91 males between the age of 18 and 79 years with a mean age of 53. Results : Apart from typical intraspinal tumours (i.e. astrocytomas and ependymomas), and extraspinal tumours, (i.e. meningiomas, schwannomas, neurofibromas), rare neoplastic and non-neoplastic tumour-like changes occur in the same localizations. These rare conditions include: capillary haemangioma, paraganglioma of filum terminale, meningeal gliomatosis, different variants of cysts such as the dermoid cyst, synovial cyst and aneurysmatic bone cyst, neoplastic and non-neoplastic bone tumours like the giant cell tumour, chordomas, and intramedullary metastatic carcinomas. Conclusions : This paper presents and discusses spinal lesions from collected data with special attention paid to the rare conditions, which are reviewed in more detail.